2017
DOI: 10.1002/lol2.10048
|View full text |Cite
|
Sign up to set email alerts
|

Ice duration drives winter nitrate accumulation in north temperate lakes

Abstract: The duration of winter ice cover on lakes varies substantially with climate variability, and has decreased over the last several decades in many temperate lakes. However, little is known of how changes in seasonal ice cover may affect biogeochemical processes under ice. We examined winter nitrogen (N) dynamics under ice using a 301 yr dataset from five oligotrophic/mesotrophic north temperate lakes to determine how changes in inorganic N species varied with ice duration. Nitrate accumulated during winter and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 59 publications
(65 reference statements)
5
60
1
Order By: Relevance
“…The variation in water chemistry between depths implies at least some degree of stratification, and thus the presence of NO 3 -N may reflect depth-specific nitrification. However, in three lakes, surface and middle NO 3 -N coincided with NH 4 -N accumulation in deep waters (Allequash, Big Musky, Sparkling, Powers et al 2017), suggesting some vertical transfer of N and/or DO, especially during late winter. Below 4.0Ā°Ā°C, water density increases as it warms (Wetzel 2001), and relatively small density gradients under ice may promote circulation (Bruesewitz et al 2014), perhaps delivering oxygenated water to benthic nitrifiers; this provides a possible explanation for the maintenance of DO concentrations above 2.5 mg L -1 in deep water of Crystal and Trout, the two deepest lakes ([ 20 m), which in turn had the highest deepwater NO 3 -N accumulation rates.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The variation in water chemistry between depths implies at least some degree of stratification, and thus the presence of NO 3 -N may reflect depth-specific nitrification. However, in three lakes, surface and middle NO 3 -N coincided with NH 4 -N accumulation in deep waters (Allequash, Big Musky, Sparkling, Powers et al 2017), suggesting some vertical transfer of N and/or DO, especially during late winter. Below 4.0Ā°Ā°C, water density increases as it warms (Wetzel 2001), and relatively small density gradients under ice may promote circulation (Bruesewitz et al 2014), perhaps delivering oxygenated water to benthic nitrifiers; this provides a possible explanation for the maintenance of DO concentrations above 2.5 mg L -1 in deep water of Crystal and Trout, the two deepest lakes ([ 20 m), which in turn had the highest deepwater NO 3 -N accumulation rates.…”
Section: Discussionmentioning
confidence: 93%
“…Following from work by Striegl et al (2001), a surge of recent research has confirmed that biogenic gases often accumulate over winter in seasonally frozen lakes (Ducharme-Riel et al 2015;Denfeld et al 2016) along with oxidized solutes including nitrate, sulfate, and carbonate/bicarbonate from methane oxidation (Gammons et al 2014;Hanson et al 2006;Powers et al 2017). These findings point to active benthic and planktonic communities (Bertilsson et al 2013;Hampton et al 2017) that affect whole-lake chemistry through sustained aerobic and anaerobic biological processes under ice-which may not be surprising given similar observations from permanently frozen lakes (Morgan-Kiss et al 2016;Powers and Hampton 2016).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Data were available for both years to compare lake These pathways that drive physical changes in lake ecosystems may also contribute to chemical changes that influence phytoplankton ( Figure 1). Earlier ice-out may lead to increased nutrient loading [34], or conversely, reductions in the duration of winter ice cover may contribute to reduced under-ice nitrate production [35], thus links between ice-out and changes in nutrients remain unclear. In addition, increased light exposure from earlier ice-out can alter dissolved organic carbon concentrations and quality [36].…”
Section: Methodsmentioning
confidence: 99%